Healthcare Utilization by Glaucoma Patients in a Team Care Model. (17th November 2018) - Damento, Gena M.; Winkler, Nelson S.; Hodge, David O.; Khanna, Sunil S.; Khanna, Cheryl L.
ABSTRACT: Purpose : To determine the effect of a glaucoma team care model on resource utilization and efficiency in glaucoma management. Methods : Retrospective cohort study of 358 patients diagnosed and treated for glaucoma. Analysis included number of patient visits, diagnostic tests, and glaucoma procedures performed before (2005–2007) and after (2008–2010) implementation of a team care model in 2008. Patients not involved in the model served as controls. Results : Number of patient visits did not change significantly after model implementation ( p > .05). Diagnostic tests significantly increased in comprehensive ophthalmologist and glaucoma subspecialist groups 25 months after diagnosis ( p = .03 and p = .001). Procedures increased for glaucoma subspecialists but was not statistically significant ( p = .06). Optometrists used billing codes with significantly lower reimbursement than other providers ( p < .001). Conclusions : Team care model had neutral effect on patient visits and increased testing. Continued evaluation of this model is required to determine its effect on disease progression and outcomes.